Development of Student Confidence Through Traditional Game Activities - Ziftahni Rachma Sukarna; Didin Budiman; Wulandari Putri (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Self-confidence is one's belief in one's ability to do something or show a certain appearance. This study used traditional games as a treatment to see the development of self-confidence in students. The traditional games used in this study include several games, namely crank, engrang, and sack race. The research design used is classroom action research. This research uses a type of quantitative descriptive approach. The instruments used in this study were used by the researchers themselves as the main instruments in the research by using tools in the field in the form of observation and documentation. This study involved students at one of the Public Elementary Schools in Bandung City, with a total sample of 36 students who were Grade V students. The results of this study showed that there was an increase in each cycle, cycle 1 action 1 getting an average score (67.38), cycle 1 action 2 getting an average value (71.05), cycle 2 action 1 getting an average value (76.72) and cycle 2 action 2 get an average value (78.85). The conclusion of the study shows that there is a development of students' self-confidence through traditional game activities, so that there is a change in the attitude of students in participating in the learning process.